#TITLE_ALTERNATIVE# - CHA TARIDO (NIM 10204008), JULI
The effect of annealing on electrical properties to study thermal stability, interface effect, and oxidation reaction of AlGaN grown on Si (111) by plasma-assisted metal-organicvapour-deposition (PA-MOCVD) method as metal-semiconductors-metal (MSM) Schottky contact was investigated. The dependence of dark current to barrier height on material properties after and before giving annealing of samples were calculated. Although the samples were grown with the same parameters and the Au evaporation process, I-V characteristic seems depend on the distribution of Al atoms in thin film that was evaluated from barrier height of each sample. After Annealling at 5000C for five minutes, I-V characteristic shown the dark current predominantly influenced by leakage current as interface effect between AlGaN and Au. The other result confirms that for giving annealing at 6000C for five minutes the dark current decrease inversly to barrier height for each sample. Maximum condition due to the lowest dark current and highest barrier height was achieved after giving annealing at 8000C for two minutes, that condition was dominated by the structure alteration at thin film. Finally, the oxidation reaction was formed at thin film surface for annealing at 8500C for four minutes by residual impurity of niyrogen gas.